THE URGENCY AND STRATEGIES OF STUDENT CHARACTER EDUCATION IN THE NEW NORMAL ERA - Mohammad Hasan (Citra Dharma Cindekia, 2022)
The occurrence of moral crisis problems among people in daily life makes character education important to be applied in Indonesia, especially in the new normal era like today. The purpose of this study is to examine more deeply about the urgency and strategy for implementing character education in the new normal era. The research method uses a literature study by seeking information related to the topic in books, journals, and proceedings on a national and international scale. The results of this study indicate that character education is very important to be applied to counteract the negative effects due to the implementation of new normal era policies. The application of character education must be innovative and creative, adapted to new normal conditions, for example by setting an example, providing education with habits, giving advice/reprimand, and giving attention and supervision.